The Colonists of Yurinaki - Plasencia Soto, Rommel (2010)
In this article display a picture of Yurinaki´s zone, in the central peruavian jungle. That in certain way appears as a rural route of setting subsidiary of the andean laborers of the farme large estate of the Peruvian Coporation and of the large wave of migrants that they test the interethnic together and the sustainable development of to country